Limiting factors of rice yield in Colombia. Final Report on the MADR - CIAT Agreement - Jiménez, Daniel; Delerce, Sylvain Jean; Dorado, Hugo (International Center for Tropical Agriculture, 2016)
The International Center for Tropical Agriculture and the Colombian Rice Association (Federación Nacional de Arroceros, FEDEARROZ) conducted a project-oriented to strength the adaptation capabilities of facing weather variability and climate change for the rice sector. One of the main objectives of this project was to improve the competences of FEDEARROZ for recording, storing and analyzing data. Emphasized on crop-environmental knowledge interaction. Through this project, both institutions carried through several analyses per locality and system. These results showed the strong influence that has the weather variables on productivity variations. In addition, FEDEARROZ passed through a training process offered by CIAT, in order to develop skills in technicians and researchers for data decision making.